PENGARUH PENERAPAN MODEL LEARNING CYCLE 5E TERHADAP HASIL BELAJAR PAI SISWA DI SMA NEGERI 4 KOTA BUKITTINGGI - Andy Riski Pratama; Deswalantri Deswalantri; Zulfani Sesmiarni; Khairuddin Khairuddin (KOLONI, 2022)
Based on observations with the PAI teacher Class XI IPS 3 at SMA NEGERI 4 BUKITTINGGI CITY, it shows that the PAI learning outcomes of students are low. The reason for this is that students are less interested and think PAI is learning to memorize. Students are only invited to imagine without any real examples and evidence of related material. PAI learning must apply creative, active, and innovative learning models so that students are actively involved in the learning process. The purpose of this study was to determine the effect of the 5E Learning Cycle Model on PAI Learning Outcomes at SMA 4 Negeri 4 Bukittinggi. This research is a quantitative research type Experimental Quansy. The subjects of this research are students of class XI IPS 3. The research sample is Class XI IPS 4 as an Experimental class with Learning Cycle 5E Learning Model, class XI IPS 3 as a control class. The data analysis technique used the Normality Test with the Shapiro Whilk test, and the Homogeneity Test with the. Followed by Hypothesis Testing with Post-Test Group t-test. Based on the results of the research that has been done, it can be concluded that the learning outcomes of students who are taught with the 5E Learning Cycle model in PAI subjects are quite good. The results of the posttest student learning are in the high category with an average value of 84.24 and the influence of the use of the Learning Cycle 5E learning model in PAI subjects on the learning outcomes of class XI students at SMA Negeri 4 Bukittinggi. This has been proven based on the results of hypothesis testing using the Paired Simple Test, which obtained a significant value of student learning outcomes, namely 0.000 <0.05.abstract should end with a comment about the importance of the result or a brief conclusion. Keywords: Learning Cycle 5E, Learning Outcomes